How Do Managers and Shareholders Respond to Taxation? An Analysis of the Introduction of the UK Real Estate Investment Trust Legislation. - Holland, Kevin; Lindop, Sarah; Abdul Wahab, Nor Shaipah (Abacus, 2022)
Corporate finance decisions, measurement of accounting profits, and market valuations are invariably made within the framework of a taxation system(s). Previous research indicates both ambiguity over the influence of taxation on managers' behaviour and limitations in the ability of shareholders to process tax information. The establishment of the UK's Real Estate Investment Trust (REIT) regime in 2006 allowed quoted companies to opt out of company level taxation. We examine managers' and shareholders' responses, that is, their ability to process information. When compared with shareholders, managers demonstrated a greater knowledge of the legislation, and of its applicability. For example, managers appeared to pre‐empt the effects of the legislation. Our findings have implications for tax policy makers and taxpayers, acting as a warning of the potential downside of increased cooperation when trying to make more appropriately formed legislation. Further, managers appeared to be willing to trade off the interests of shareholders for their own personal gain, which is surprising given the visibility of the REIT conversion process and illustrates the limitations of shareholder control over managers' behaviour. We find shareholders were able to accurately assess the general effects of the legislation but were unable to identify specific companies likely to benefit. Without any increase in shareholder sophistication, concerns exist over the effectiveness of shareholders in acting as monitors of managers' decision making.